Исследования динамики процесса прессования металлического порошка на вибростоле с «жесткой» матрицей и одновременным статическим пригружением - Савелов, Д. В. (НТУ "ХПИ", 2014)
В статье предложена математическая модель динамической системы «вибростол-металлический порошок-пригружающий пуансон», в которой металлический порошок представлен в виде системы с распределенными параметрами. Дифференциальное уравнение движения в своем составе учитывает трение слоев порошка и его распределяющую способность. Получены теоретические выражения, описывающие закономерности движения прессуемого металлического порошка, вибростола с «жесткой» матрицей и пуансона с учетом действующего усилия пригружения

In the article the mathematical model of the dynamic system is offered «vibration table is metallic powder is a prigruzhajut puncheon», in which metallic powder is presented as a system with the up-diffused parameters. Using the known method of reactions, it was worked out a differential wave equation of vibrations. Differential equalization of motion in the structure takes into account physical and mechanical descriptions of metallic powder, friction of layers of powder and his distributing ability. Theoretical expressions which describe conformities to law of motion of the pressed metallic powder are got, vibration table with a «hard» matrix and puncheon taking into account operating effort of prigruzhennye. Practical recommendations are given on application of technology of preliminary compression with simultaneously operating static prigruzhennye
Researh of dynamiсs of process of pressing of metallic powder on vibrating table with a «hard» matrix an dsimultaneous static pressing
Keywords: математическая модель; динамическая система; пуансон; трение; mathematical model; dynamic system; vibration table; puncheon